ONCOLOGISTS' BARRIERS AND FACILITATORS FOR ONCOTYPE DX USE: QUALITATIVE STUDY. (13th December 2016) - Roberts, Megan C.; Bryson, Amy; Weinberger, Morris; Dusetzina, Stacie B.; Dinan, Michaela A.; Reeder-Hayes, Katherine; Wheeler, Stephanie B.
Abstract : Background: Oncotype DX (ODX), a tumor gene profiling test, has been incorporated into clinical guidelines to aid in adjuvant chemotherapy decision making for early-stage, hormone receptor positive breast cancer patients. Despite United States (U.S.) guidelines, less than half of eligible women receive testing. Reasons for low usage are unclear: Our objective was to better understand U.S. oncologists' ODX uptake and how they use ODX during adjuvant chemotherapy decision making. Methods: We conducted semi-structured, 30-minute phone interviews with medical and surgical oncologists in one U.S. State using purposive sampling. Oncologists were included if they saw greater than or equal to five breast cancer patients per week. Recruitment ended upon thematic saturation. Interviews were recorded, transcribed, and double-coded using template analysis. Results: During analysis, themes emerged across three domains. First, organizational factors (i.e., departmental structure, ODX marketing, and medical/insurance guidelines) influenced ease of ODX use. Second, oncologists referenced the influence of interpersonal factors (e.g., normative beliefs and peer use of ODX) over their own practices and recommendations. Third, intrapersonal factors (e.g., oncologist attitudes, perceived barriers, and research gaps) were discussed: although oncologists largely held positive attitudes about ODX, they reported challenges with interpreting intermediate scores for treatment decisions and explaining test results to patients. Finally, oncologists identified several research gaps. Conclusions: As more tumor gene profiling tests are incorporated into cancer care for treatment decision making, it is important to understand their use in clinical practice. This study identified multi-level factors that influence ODX uptake into clinical practice, providing insights into facilitators and modifiable barriers that can be leveraged for improving ODX uptake to aid treatment decision making.